Who Adopts LPG as the Main Cooking Fuel and Why? Empirical Evidence on Ghana Based on National Survey. (September 2016) - Karimu, Amin; Mensah, Justice Tei; Adu, George
Highlights: Socioeconomic and demographic factors are consistently key drivers. Linear specification for income, age, and household size is inappropriate. An imposed linear specification tends to bias the estimates. Price is important but its exclusion does not significantly bias the estimates. A subsidy on LPG and a tax on charcoal will be effective for urban dwellers. Summary: The aim of this paper is to identify the factors that influence the probability of adopting LPG as the main cooking fuel in Ghana using household level data gleaned from last two nationwide household surveys (GLSS 5 & GLSS 6). Using a flexible semi-parametric specification, the following were uncovered. First, we find socioeconomic and demographic factors such as income, education, access to urban infrastructure, and location of household, as key drivers of households' choice of LPG as main cooking energy source. Again the influences of these factors are stable across time, and with a strong price effect. The evidence shows that urban households with better socioeconomic and demographic factors are likely to adopt LPG as the main cooking fuel relative to households in rural areas and also urban households with poor socioeconomic and demographic factors. Finally, we observe that the imposition of fully parametric structure (functional form) prior to estimation on factors such as age of household head, income, and household size as done in the literature is inappropriate, at least in the case of Ghana and tend to bias the marginal effects. There is strong evidence of variations in the response rate of LPG adoption over the domains of income, household size, and the age of the household head. The results suggest a policy dichotomy between rural and urban dwellers for it to be effective.